Catalyst slurry for fuel cells and method for producing same

The catalyst slurry for fuel cells, utilizing an electrocatalyst with micropores and a dual-ionomer layer with varying equivalent weights, addresses the challenge of maximizing the three-phase interface, thereby enhancing water discharge and carbon corrosion resistance.

JP7657001B2Active Publication Date: 2025-04-04HYUNDAI MOTOR CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020149385
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-09-04
Publication Date
2025-04-04
Estimated Expiration
2040-09-04

AI Technical Summary

Technical Problem

Existing fuel cell catalyst systems struggle to maximize the three-phase interface within the electrode, leading to suboptimal water discharge characteristics and carbon corrosion durability.

Method used

A catalyst slurry for fuel cells is developed, featuring an electrocatalyst with micropores and an ionomer layer composed of two ionomers with different equivalent weights (EW). The first ionomer with a lower EW is applied to the outer surface for hydrogen ion conductivity, while the second ionomer with a higher EW is applied to the inner surface of mesopores for enhanced water discharge.

Benefits of technology

This approach maximizes the three-phase interface, significantly improving water discharge characteristics and enhancing the durability against carbon corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657001000001
    Figure 0007657001000001
  • Figure 0007657001000002
    Figure 0007657001000002
  • Figure 0007657001000003
    Figure 0007657001000003
Patent Text Reader

Abstract

To provide a catalyst slurry and a method for manufacturing the same in which advantages of two kinds of ionomers having different equivalent weights (EWs) are combined so as to maximize a 3-phase boundary in an electrode and improve discharge characteristics of generated water and carbon corrosion durability.SOLUTION: A catalyst slurry for fuel cells includes an electrode catalyst formed as catalyst particles including micropores, and an ionomer layer formed on the electrode catalyst. The electrode catalyst includes an outer surface, and mesopores formed to extend inwards from the outer surface to a predetermined depth. The ionomer layer includes a first ionomer formed on the outer surface of the electrode catalyst in which the micropores are located, and a second ionomer formed on inner surfaces of the mesopores, the average length of side chains of the second ionomer being longer than an average length of side chains of the first ionomer.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst slurry for a fuel cell and a method for producing the same. [Background technology]

[0002] In the case of polymer fuel cells for vehicles, it is necessary to have technology to design electrode catalyst layers that can ensure optimal performance under various operating conditions (temperature / humidity) and can properly discharge water generated when the fuel cell is in operation to prevent flooding.

[0003] The ionomer contained in the cathode electrode catalyst layer plays a role in transferring hydrogen ions that react with oxygen to generate electricity. The lower the equivalent weight (EW) of the ionomer, the more ion exchange groups there are, which is favorable for hydrogen ion conduction, but the weaker the water discharge characteristics of the generated water, whereas the higher the equivalent weight, the less favorable it is for hydrogen ion conduction, but the stronger the water discharge characteristics are.

[0004] As such, various technological developments and inventions have been reported that can utilize two types of ionomers with different EWs in order to compensate for the drawbacks of a specific ionomer equivalent weight (EW) while maximizing its advantages (US2018-0254489A1, WO2018-064623A1), but the effects are limited and restrictive because the two types of ionomers are simply mixed or made into separate layers. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] US Patent Publication No. 2018-0254489A1 [Patent Document 2] International Patent Publication No. WO2018-064623A1 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide a catalyst slurry and its manufacturing method that can maximize the three-phase interface in the electrode by combining the advantages of two types of ionomers with different equivalent weights (EW), and improve the water discharge characteristics of the produced water and the carbon corrosion resistance.

[0007] The object of the present invention is not limited to the object mentioned above. The object of the present invention will become clear from the following description and can be realized by the means and combinations thereof described in the claims. [Means for solving the problem]

[0008] A catalyst slurry for a fuel cell according to an embodiment of the present invention includes an electrode catalyst formed of catalyst particles having micropores, and an ionomer layer formed on the electrode catalyst, the electrode catalyst including an outer surface and mesopores recessed from the outer surface to an interior portion at a predetermined depth, the ionomer layer including a first ionomer formed on an outer surface of the electrode catalyst where the micropores are located, and a second ionomer formed on an inner surface of the mesopores, and an average length of side chains of the second ionomer is longer than an average length of side chains of the first ionomer.

[0009] The catalyst particles may include a support on which a catalytic metal is supported.

[0010] The catalytic metal may include those selected from the group consisting of platinum (Pt), palladium (Pd), iridium (Ir), rhodium (Rh), gold (Au), silver (Ag), cobalt (Co), nickel (Ni), and combinations thereof.

[0011] The support may comprise a material selected from the group consisting of carbon black, acetylene black, ketjen black, activated carbon, carbon nanotubes, carbon nanofibers, carbon nanowires, and combinations thereof.

[0012] The support may include micropores having a size of less than 2 nm.

[0013] The catalyst particles may have a particle size of 1 μm or less.

[0014] The mesopores may include pore openings that open from the interior of the electrode catalyst to the exterior and intersect with the outer surface of the electrode catalyst, and the pore openings may have a diameter of 2 nm to 50 nm and a recessed depth of 2 nm to 200 nm.

[0015] The first ionomer has an equivalent weight (EW) of 400 to 800 and may include one selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof.

[0016] The second ionomer has an equivalent weight of 800 to 1,200 and may include one selected from the group consisting of polysulfone-based resins, polyether ketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof.

[0017] The second ionomer may also be formed on the outer surface of the electrocatalyst where the micropores are located.

[0018] The electrode catalyst may further include a water electrolysis catalyst supported on the inner surface of the mesopores, the water electrolysis catalyst being mixed with the second ionomer, and the water electrolysis catalyst may include a metal catalyst or an oxide thereof selected from the group consisting of iridium (Ir), ruthenium (Ru), and combinations thereof.

[0019] The amount of the water electrolysis catalyst supported may be 10 parts by weight to 50 parts by weight based on 100 parts by weight of the electrode catalyst.

[0020] A method for preparing a catalyst slurry for a fuel cell according to an embodiment of the present invention may include the steps of: preparing a starting material including catalyst particles, a first ionomer, and a pore-former; obtaining an intermediate product in which an outer surface of a composite including the catalyst particles and the pore-former is coated with the first ionomer by heat-treating the starting material; removing the pore-former from the intermediate product to obtain an electrode catalyst having mesopores formed therein; and coating an inner surface of the mesopores with a water electrolysis catalyst and a second ionomer.

[0021] The pore-forming agent may contain silica having a particle size of 5 nm to 50 nm.

[0022] The content of the pore-forming agent may be 10 to 50 parts by weight based on 100 parts by weight of the catalyst particles.

[0023] The starting material can include 60% to 80% by weight of catalyst particles and pore former, and 20% to 40% by weight of a first ionomer.

[0024] The starting material can be prepared by dispersing the catalyst particles and pore-forming agent in a solvent and then dispersing the first ionomer in the resultant.

[0025] The starting material can be heat-treated at 100° C. to 140° C. for 2 to 4 hours to obtain an intermediate product.

[0026] The pore-forming agent can be removed by placing the intermediate product in an alkaline solution and refluxing it.

[0027] The production method can coat the inner surfaces of the mesopores of the electrode catalyst with the second ionomer by dispersing the electrode catalyst, the water electrolysis catalyst, and the second ionomer in a dispersion solvent. Effect of the Invention

[0028] The catalyst slurry according to the present invention has excellent water discharge characteristics for produced water and excellent carbon corrosion resistance.

[0029] The catalyst slurry according to the present invention can maximize the three-phase interface in the electrode.

[0030] The effects of the present invention are not limited to those mentioned above, and should be understood to include all effects that can be inferred from the following description. [Brief description of the drawings]

[0031] [Figure 1] FIG. 1 is a schematic diagram of an electrocatalyst slurry according to the prior art. [Diagram 2] FIG. 2 is a diagram showing a catalyst slurry for a fuel cell according to the present invention. [Diagram 3] FIG. 3 is a diagram showing the catalyst particle of FIG. [Figure 4] FIG. 4 is a diagram showing an electrode catalyst formed by agglomeration of the catalyst particles of FIG. [Diagram 5] 2 is a flow chart showing a method for producing the catalyst slurry according to the present invention. [Figure 6] 2A-2C show intermediate products formed during the manufacturing process. [Figure 7] FIG. 2 is a reference diagram for explaining the formation of mesopores by removing the pore-forming agent from the intermediate product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The above objects, other objects, features and advantages of the present invention will be easily understood from the following preferred embodiments based on the accompanying drawings. However, the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments described herein are provided so that the disclosure will be thorough and complete, and so that the concept of the present invention will be fully conveyed to those skilled in the art.

[0033] In the description of each figure, like reference numerals are used for like elements. In the accompanying drawings, the dimensions of structures are exaggerated for clarity of the present invention. Terms such as first and second may be used to describe various elements, but the elements should not be limited to the terms. The terms are used only for the purpose of distinguishing one element from another element. For example, the first element may be called the second element, and the second element may be called the first element, without departing from the scope of the present invention. A singular expression includes a plural expression unless the context clearly dictates otherwise.

[0034] In this specification, the terms "comprise" or "have" are intended to specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, and should be understood as not precluding the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof. In addition, when a layer, film, region, plate, or other part is said to be "on" another part, this does not only include the case where it is "directly on" the other part, but also includes the case where there is another part between them. Conversely, when a layer, film, region, plate, or other part is said to be "under" another part, this does not only include the case where it is "directly under" the other part, but also includes the case where there is another part between them.

[0035] Unless otherwise indicated, all numbers, values ​​and / or expressions expressing amounts of ingredients, reaction conditions, polymer compositions and formulations used herein should be understood in all cases to be modified by the term "about" since such numbers are inherently approximations reflecting, among other things, the various uncertainties of measurement that arise in obtaining such values. Also, when numerical ranges are disclosed in the following description, such ranges are continuous and include all values ​​from the minimum value to the maximum value, inclusive, unless otherwise indicated. Furthermore, when such ranges refer to integers, they include all integers from the minimum value to the maximum value, inclusive, unless otherwise indicated.

[0036] Ionomers used in fuel cell electrodes are components that transfer hydrogen ions within the electrode. The properties of the ionomers change depending on their equivalent weight (EW), so it is important to decide which ionomer to use to construct the electrode. Specifically, if the ionomer has a low equivalent weight (EW), it has many ion exchange groups, which is advantageous for hydrogen ion conduction, but is highly hydrophilic and does not allow water to be discharged smoothly. Conversely, if the equivalent weight (EW) is high, it is not advantageous for hydrogen ion conduction, but is highly hydrophobic and allows water to be discharged smoothly. Therefore, a technology has been proposed to construct electrodes using two types of ionomers with different equivalent weights (EW).

[0037] 1 is a schematic diagram of an electrode catalyst slurry according to the prior art. Specifically, an ionomer 70 with a low equivalent weight (EW) and an ionomer 80 with a high equivalent weight (EW) are mixed and then coated on an electrode catalyst 90. However, in this case, the ionomers 70 and 80 are randomly attached to the surface of the electrode catalyst 90, so the effect obtained is limited.

[0038] The present invention overcomes the limitations of the prior art by using two types of ionomers with different equivalent weights (EW), and is characterized by allowing each ionomer to be formed in an appropriate position to maximize its functionality.

[0039] 2 is a diagram showing a catalyst slurry for a fuel cell according to the present invention. Referring to this figure, the catalyst slurry includes an electrode catalyst 10 in which catalyst particles 11 are aggregated, and an ionomer layer 20 formed on the electrode catalyst 10.

[0040] 3 is a diagram showing the catalyst particle 11. Referring to this, the catalyst particle 11 may include a support 112 on which a catalyst metal 111 is supported.

[0041] The catalytic metal 111 may include a metal selected from the group consisting of platinum (Pt), palladium (Pd), iridium (Ir), rhodium (Rh), gold (Au), silver (Ag), cobalt (Co), nickel (Ni), and combinations thereof.

[0042] The support 112 may include a material selected from the group consisting of carbon black, acetylene black, ketjen black, activated carbon, carbon nanotubes, carbon nanofibers, carbon nanowires, and combinations thereof.

[0043] The support 112 may include micropores 112a having a size of less than 2 nm.

[0044] The particle size of the catalyst particle 11 is not particularly limited and may be, for example, 1 μm or less. The particle size of the catalyst particle 11 may refer to the distance from one point on the surface of the catalyst particle 11 to another point on the opposite surface. If the particle size of the catalyst particle 11 exceeds 1 μm, the mesopores 12 of the electrode catalyst 10 described below may not be smoothly formed.

[0045] FIG. 4 is a diagram showing an electrode catalyst 10 formed by agglomeration of the catalyst particles 11. As shown in FIG.

[0046] The electrode catalyst 10 may include an outer surface and mesopores 12 formed by indenting from the outer surface toward the inside to a predetermined depth.

[0047] The shape of the mesopores 12 is not particularly limited, and may be, for example, a kind of channel shape formed by extending from the outer surface of the electrode catalyst 10 toward the inside as shown in FIG. 4, or may be a shape close to a hemisphere.

[0048] Specifically, the mesopores 12 include pore openings that open from the inside of the electrode catalyst 10 to the outside and intersect with the outer surface of the electrode catalyst 10, and the pore openings may have a diameter of 2 nm to 50 nm and a recessed depth of 2 nm to 200 nm.

[0049] The mesopores 12 function as a passage for discharging water generated during the operation of the fuel cell. Therefore, it is preferable that an ionomer, which is advantageous for discharging water, is located in the mesopores 12. Meanwhile, the catalyst particles 11, more precisely, micropores 112a resulting from the support 112, are located on the outer surface of the electrode catalyst 10. Since the metal catalyst is supported in the micropores 112a, it is preferable that an ionomer, which has superior hydrogen ion conductivity rather than water discharge, is located around the micropores 112a.

[0050] In view of this, in the present invention, as shown in FIG. 2, a first ionomer 21 having a short average side chain length, a small equivalent weight (EW), and high hydrogen ion conductivity is in contact with the outer surface of the electrode catalyst 10, and a second ionomer 22 having a long average side chain length, a large equivalent weight (EW), and smooth water discharge is in contact with the mesopores 12.

[0051] Specifically, the first ionomer 21 has an equivalent weight (EW) of 400 to 800 and may include one selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof. The first ionomer 21 has a short average length of side chains, and can smoothly contact the catalytic metal 111 supported in the micropores 112a, and has high hydrogen ion conductivity. However, the first ionomer 21 is highly hydrophilic, which is disadvantageous in terms of water discharge.

[0052] The second ionomer 22 has an equivalent weight of 800 to 1,200 and may include a resin selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof. The second ionomer 22 has a long side chain and is hydrophobic, which is advantageous for water discharge. However, the contact with the catalytic metal 111 supported in the micropores 112a is significantly poor.

[0053] The electrode catalyst 10 may further include a water electrolysis catalyst 13 supported on the inner surface of the mesopores 12. As described above, the mesopores 12 serve as paths for water discharge, and the water may corrode the support 112. Another feature of the present invention is that the water electrolysis catalyst 13 is applied to the inner surface of the mesopores 12 to prevent the above-mentioned problems from occurring.

[0054] The water electrolysis catalyst 13 is not particularly limited, and may include, for example, a metal catalyst selected from the group consisting of iridium (Ir), ruthenium (Ru), and combinations thereof, or an oxide thereof.

[0055] The supported amount of the water electrolysis catalyst 13 may be 10 parts by weight to 50 parts by weight based on 100 parts by weight of the electrode catalyst 10.

[0056] 5 is a flow chart showing a method for preparing the catalyst slurry according to the present invention. Referring to the figure, the method includes the steps of preparing starting materials including catalyst particles, a first ionomer, and a pore-forming agent (S10), heat-treating the starting materials to obtain an intermediate product in which the outer surface of a composite including the catalyst particles and the pore-forming agent is coated with the first ionomer (S20), removing the pore-forming agent from the intermediate product to obtain an electrode catalyst having mesopores formed therein (S30), and coating the inner surfaces of the mesopores with a second ionomer (S40).

[0057] The method for preparing the electrode catalyst is characterized in that mesopores are formed in the electrode catalyst and appropriate ionomers are added during the process, so that each ionomer can be formed at a desired position, as will be described in detail below.

[0058] 6 is a diagram showing the intermediate product. The intermediate product can be obtained by heat treating starting materials including catalyst particles 11, a first ionomer 21, and a pore-forming agent 30 (S20).

[0059] The pore-forming agent 30 may include silica having a particle size of 5 nm to 50 nm. If the particle size is less than 5 nm, the size of the formed mesopores may be too small, making it difficult to remove the pore-forming agent 30. On the other hand, if the particle size exceeds 50 nm, the size of the mesopores may be too large, resulting in a decrease in the number of mesopores and a decrease in the specific surface area of ​​the electrode catalyst.

[0060] The content of the pore-forming agent 30 is not particularly limited, and may be, for example, 10 to 50 parts by weight based on 100 parts by weight of the catalyst particles 11.

[0061] In addition, the starting material may contain 60% to 80% by weight of the catalyst particles and the pore-forming agent, and 20% to 40% by weight of the first ionomer. When the content of each component is as described above, mesopores can be formed with an appropriate size and fraction.

[0062] Alternatively, the starting material may be prepared by dispersing the catalyst particles 11 and the pore-forming agent 30 in a solvent and then dispersing the first ionomer 21 in the resultant mixture so that the first ionomer 21 is coated on the outer surface, not the inside, of the composite of the catalyst particles 11 and the pore-forming agent 30, as shown in FIG 5.

[0063] The solvent is not particularly limited, and may be, for example, a solvent selected from the group consisting of distilled water, ethanol, propanol, and combinations thereof.

[0064] Prior to the heat treatment of the starting material, a step of drying the starting material may be further carried out. Specifically, the starting material may be dried at 60°C to 90°C for 12 hours or more using a drying device such as an oven. If the drying temperature is too low, the solvent may not be dried sufficiently, and conversely, if the drying temperature is too high, the drying speed may be too fast and the catalyst may ignite.

[0065] Then, the starting material is heat-treated at 100° C. to 140° C. for 2 to 4 hours to obtain an intermediate product. If the heat treatment temperature is less than 100° C., the first ionomer 21 may not be properly attached to the surface of the metal catalyst since it is lower than the glass transition temperature (Tg) of the first ionomer 21, and if the heat treatment temperature exceeds 140° C., the structure of the ionomer and catalyst may be destroyed due to excessive heat.

[0066] Thereafter, as shown in FIG. 7, the pore-forming agent may be removed from the intermediate product to form mesopores (S30).

[0067] Specifically, the pore-forming agent can be removed by refluxing the intermediate product in an alkaline solution, whereby the first ionomer coated on the surface of the pore-forming agent is also removed.

[0068] The alkaline solution can be obtained by dissolving a hydroxide of an alkali metal or an alkaline earth metal in distilled water. Here, an alkaline solution with an appropriate molar concentration can be prepared so that the pore-forming agent can be sufficiently dissolved. When particulate silica is used as the pore-forming agent, the molar concentration of the alkaline solution is preferably in the range of about 3M to 10M.

[0069] The reflux conditions are not particularly limited, and may be, for example, refluxing the alkaline solution containing the intermediate product at a temperature of 50° C. to 95° C. for 2 hours to 5 hours.

[0070] The resultant product of the above steps is washed and dried to obtain an electrode catalyst having mesopores. As shown in FIG. 7, the electrode catalyst has a first ionomer 21 formed on its outer surface.

[0071] Then, the mesopores 12 of the electrode catalyst as shown in FIG. 7 are coated with a second ionomer 22 to obtain the catalyst slurry according to the present invention as shown in FIG.

[0072] Specifically, the electrode catalyst and the second ionomer 22 may be dispersed in a solvent to coat the mesopores 12 with the second ionomer 22 .

[0073] The solvent is not particularly limited, and may be, for example, a solvent selected from the group consisting of distilled water, ethanol, propanol, and combinations thereof.

[0074] Here, by adding the above-mentioned water electrolysis catalyst 13 together, the water electrolysis catalyst 13 can be supported on the mesopores 12.

[0075] The catalyst slurry according to the present invention can be used to manufacture a fuel cell electrode. The method for manufacturing the electrode is not particularly limited, and the catalyst slurry can be coated on a substrate such as a release paper or an electrolyte membrane by a method such as spray coating, bar coating, slot die coating, etc. to obtain an electrode.

[0076] Although the embodiments of the present invention have been described above with reference to the accompanying drawings, it will be understood by those skilled in the art that the present invention can be embodied in other specific forms without changing the technical concept or essential features of the present invention. Therefore, it should be understood that the embodiments described above are illustrative in all respects and are not limiting. [Explanation of symbols]

[0077] 10 Electrocatalyst 11 Catalytic particles 111 Catalytic metals 112 Support 112a Micropores 12 Mesopores 13 Water electrolysis catalyst 20 Ionomer layer 21 First Ionomer 22 Second Ionomer

Claims

1. an electrocatalyst formed from catalytic particles containing micropores; an ionomer layer formed on the electrode catalyst; The electrode catalyst includes an outer surface and mesopores formed from the outer surface toward the inside at a predetermined depth, The ionomer layer includes a first ionomer formed on a portion of an outer surface of the electrode catalyst where the mesopores are not formed, and not formed on inner surfaces of the mesopores, and a second ionomer formed on inner surfaces of the mesopores, The catalyst particles include a support on which a catalyst metal is supported, The support contains micropores having a size of less than 2 nm; A catalyst slurry for a fuel cell, wherein an average length of a side chain of the second ionomer is longer than an average length of a side chain of the first ionomer.

2. 2. The fuel cell catalyst slurry of claim 1, wherein the catalytic metal comprises one selected from the group consisting of platinum (Pt), palladium (Pd), iridium (Ir), rhodium (Rh), gold (Au), silver (Ag), cobalt (Co), nickel (Ni), and combinations thereof.

3. 2. The fuel cell catalyst slurry of claim 1, wherein the support comprises a material selected from the group consisting of carbon black, acetylene black, ketjen black, activated carbon, carbon nanotubes, carbon nanofibers, carbon nanowires, and combinations thereof.

4. 2. The catalyst slurry for a fuel cell according to claim 1, wherein the catalyst particles have a particle size of 1 μm or less.

5. 2. The catalyst slurry for fuel cells according to claim 1, wherein the mesopores include pore entrances that open from the inside of the electrode catalyst to the outside and intersect with an outer surface of the electrode catalyst, the pore entrances having a diameter of 2 nm to 50 nm and a recessed depth of 2 nm to 200 nm.

6. 2. The catalyst slurry for a fuel cell according to claim 1, wherein the first ionomer has an equivalent weight (EW) of 400 to 800 and is selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof.

7. 2. The catalyst slurry for a fuel cell according to claim 1, wherein the second ionomer has an equivalent weight of 800 to 1,200 and is selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof.

8. The fuel cell catalyst slurry according to claim 1 , wherein the second ionomer is also formed on an outer surface of the electrode catalyst where the micropores are located.

9. 2. The catalyst slurry for a fuel cell according to claim 1, wherein the electrode catalyst further comprises a water electrolysis catalyst supported on the inner surface of the mesopores, the water electrolysis catalyst being mixed with the second ionomer, and the water electrolysis catalyst comprises a metal catalyst or an oxide thereof selected from the group consisting of iridium (Ir), ruthenium (Ru), and combinations thereof.

10. 10. The catalyst slurry for a fuel cell according to claim 9, wherein the amount of the water electrolysis catalyst supported is 10 parts by weight to 50 parts by weight based on 100 parts by weight of the electrode catalyst.

11. providing starting materials including catalyst particles, a first ionomer, and a pore former; heat-treating the starting material to obtain an intermediate product in which the first ionomer is coated on an outer surface of a composite including the catalyst particles and the pore-forming agent; removing the pore-forming agent from the intermediate product to obtain an electrode catalyst having mesopores formed therein; and coating the inner surfaces of the mesopores with a water electrolysis catalyst and a second ionomer.

12. The method for producing a catalyst slurry for a fuel cell according to claim 11, wherein the pore-forming agent contains silica having a particle size of 5 nm to 50 nm.

13. 12. The method of claim 11, wherein the content of the pore-forming agent is 10 to 50 parts by weight based on 100 parts by weight of the catalyst particles.

14. 12. The method for producing a catalyst slurry for a fuel cell according to claim 11, wherein the starting material comprises 60% to 80% by weight of catalyst particles and a pore-forming agent, and 20% to 40% by weight of a first ionomer.

15. 12. The method of claim 11, wherein the starting material is prepared by dispersing the catalyst particles and the pore-forming agent in a solvent, and then dispersing the first ionomer in the resultant.

16. The method for producing a catalyst slurry for a fuel cell according to claim 11, wherein the starting material is heat-treated at 100° C. to 140° C. for 2 hours to 4 hours to obtain an intermediate product.

17. The method for producing a catalyst slurry for a fuel cell according to claim 11, wherein the pore-forming agent is removed by introducing the intermediate product into an alkaline solution and refluxing the solution.

18. 12. The method for producing a catalyst slurry for a fuel cell according to claim 11, wherein the electrode catalyst, the water electrolysis catalyst, and the second ionomer are dispersed in a dispersion solvent to coat the inner surfaces of mesopores of the electrode catalyst with the second ionomer.

Citation Information

Patent Citations

  • Method of manufacturing gas diffusion electrode and method of manufacturing solid polymer fuel cell

    JP2002184414A

  • Electrode catalyst layer for solid high polymer fuel cell, electrode for solid high polymer fuel cell, and solid high polymer fuel cell

    JP2005032668A

  • Ink for catalyst layer formation and electrode using the same and membrane electrode junction

    JP2005108827A

  • Method of manufacturing catalyst support body for polymer electrolyte fuel cell, and polymer electrolyte fuel cell

    JP2008041498A

  • Catalyst, method for producing the same, and electrode catalyst layer using catalyst

    JP2017212217A